Two‐dimensional knee valgus displacement as a predictor of patellofemoral pain in adolescent females. (29th December 2015) - Holden, S.; Boreham, C.; Doherty, C.; Delahunt, E.
Abstract : Patellofemoral pain (PFP) is a prevalent lower limb musculo‐skeletal injury in adolescent females. Female athletes with PFP display increased frontal plane knee joint motion in comparison to control subjects. The current investigation aimed to determine prospectively whether two‐dimensional knee valgus displacement during landing could predict the risk of developing PFP. Seventy‐six injury‐free adolescent female athletes (age = 12.9 ±0.35 years) participated. At baseline participants performed three drop vertical jump trials from a 31‐cm box. A standard video camera was used to record frontal plane knee joint kinematics. Over the 24‐month follow‐up, eight participants developed PFP, as diagnosed by a Chartered Physiotherapist. Knee valgus displacement was significantly increased in those who developed PFP compared to those who did not (mean difference = 7.79°; P = 0.002; partial eta squared = 0.07). Knee valgus displacement ≥10.6° predicted PFP with a sensitivity of 0.75 and specificity of 0.85. The associated positive likelihood ratio was 5. These results have clinical utility suggesting that two‐dimensional analysis could be implemented to screen for increased risk of PFP in adolescent female athletes.